Curriculum to Enhance Life Skills and Personal Growth among COVID-19 Pandemic Situation - Jiraporn Chano,; Jidapa Poogpan,; Utis Bhongchirawattana,; Bussayarat Nithideechaiwarachok, (Journal of Educational Issues, 2024)
Life skills and personal growth in education are crucial skills and students’ core competencies to learn in this modern world. The objectives of this research were 1) to study the guidelines for developing life skills and personal growth, 2) to develop a curriculum to enhance life skills and personal growth in the situation of the coronavirus disease 2019 pandemic 3) to study the results of implementing the curriculum to enhance life skills and personal growth. The participants were 39 primary school students from a small school in Mahasarakham province. The research tools included the curriculum for enhancing life skills and personal growth, managing learning, and an observation form on life skills behavior and personal growth. The results of the study showed that 1) guidelines for developing learner competency at the basic education level on life skills and personal growth; 2) a curriculum to enhance life skills and personal growth consists of the background of the curriculum, course objectives, content arrangement, activities, measurement, and evaluation for elementary school students in the situation of the coronavirus disease 2019. The content consists of learning about the pandemic, making alcohol gel, creative problem solving, positive communication, media use, and emotional control; 3) the learners who received training from the curriculum to enhance their life skills and their own prosperity have a level of practice in life skills and personal growth at a high level. It could be stated that enhancing life skills and personal growth should encourage students in their learning development.